Unspoken Meanings in the Miyowor Folktale: A Discourse AnalysisBased on Grimes’ Framework of Non-Event Information - Suabey, Rinetha Stella (Jurnal Syntax Transformation, 2025)
This study analyzes the folktale Miyowor from the Wandamen community in Teluk Wondama, West Papua, through discourse analysis with a particular emphasis on non-event information as conceptualized by Grimes. Non-event information encompasses elements such as setting, background, evaluation, and collateral details, which do not directly narrate events but enrich the overall meaning of the story. The purpose of this research is to identify the occurrence of these elements in the Miyowor folktale and to explain how they contribute to a deeper understanding of the narrative. The findings show that all four types of non-event information are present, shaping the story’s structure and revealing significant cultural values of the Wandamen people. These values include their perception of time, the importance of hard work, and the harmonious relationship between humans and nature. By uncovering these unspoken dimensions, the study demonstrates how folktales serve as a medium of cultural knowledge and identity preservation.